Debating eponyms: History of ear and eye anatomical eponyms - Kevlian Andrew; Sarah Logie; Robert Hage (Elsevier, 2023)
Structured Abstract: Background: Eponyms have historically been used in different fields like literature, law, and various sciences including medicine. The continued use of eponyms in medicine has been debated for quite some time. The authors undertook a study to identify the anatomical eponyms in the human body, and to review the literature on the eponym debate. Methods: Internet databases like Google (e.g., Scholar), Wikipedia, Whonamedit and online and print dictionaries were used to identify anatomical eponyms in the human body. During the search, the scope of the study was narrowed to eponyms related to ear and eye structures due to the high concentration of names associated with these organs. Eponyms were cross-referenced across different resources, vetted using inclusion and exclusion criteria and sorted into tables. Results: A total of 169 anatomical eponyms related to ear and eye structures were found. These names were derived from 111 persons, all of whom were male. Most of the eponymous individuals were of German descent and lived during the 19th century. Some anatomical eponyms for the ear and eye provided evidence of both the positive and negative attributes of eponyms in medicine. Conclusion: The ear and eye were found to have the largest number of associated anatomical eponyms in relation to their size. These eponyms did demonstrate some instances where confusion, miscommunication or misleading information could cause problems. Regardless of these issues, the usefulness of many eponyms is also evident. The pervasiveness and notoriety of eponyms make it almost impossible to eliminate the use of eponyms in medicine. Anatomical eponyms should therefore be used as key stop points to discuss the historical achievements in science that they represent.